(untitled) (Research, Society and Development, 2020)
Objectives: To analyze the time and movements performed by nurses when changing personal protective equipment during 12-hour shifts with people contaminated by COVID-19 and; Discuss the implications of vesting with personal protective equipment for nurses in the practice of caring for people contaminated by COVID-19. Methodology: This is a study based on the method of video film analysis, conducted in the months of April and May 2020. The method allows the evaluation of procedures, practical situations or eventualities in the images produced, understanding that the image is configured pre-text component for reflection and, looking for significant elements that represent certain traits of social life. Results: Evidence of the need to perform hundreds of repetitive movements so that the changes of entry and exit of the shift are possible, in addition to exchanges to eat and do your physiological needs, requiring physical effort and emotional exhaustion, associated with the lack of protective resources individual risk, imminent risks of contracting the disease and fear of dying. Conclusion: Florence Nightingale was right when she stated that Nursing is the main barrier of protection for patients, however, for the Nursing team to act on the frontline of care in the current pandemic, the availability of personal protective equipment is an essential condition Promoting the safety of these professionals and controlling the spread of the disease in the environment, as well as providing favorable conditions for nature to exercise its role in curing people infected by the virus.